Geocronologia U-Pb em zircão no Granodiorito Anil, Província Borborema - CE - SILVA, Thays Ferreira da (2020)
The Borborema Province, inserted in the context of the Pan-African / Brasilian Cycle, was formed as a result of the convergence between the cratons of Amazonas, West Africa-São Luís and São Francisco-Congo during the amalgamation period of West Gondwana. Associated with the Brasilian Cycle there is a huge and diverse granitic magmatism that over the last decades has been the subject of several geochronological studies. Anil Granodiorito is a batholith with an area of approximately 350 km2, geographically located in the northwestern portion of the state of Ceará, covering the eastern portion of Folha Ipu and west of Folha Santa Quitéria. The pluton has an elongated and elliptical shape, and is inserted in the Central Ceará Domain of the Northern Subprovince of the Borborema Province. Until the execution of this work, there were no dating records using the U-Pb method in zircon, therefore, this course conclusion work performed the dating of the Anil Granodiorite applying this geochronological method using a mass spectrometer with inductively coupled plasma and system multi-collector sensor connected to a laser ablation probe (LA-MC-ICP-MS). Thus, we sought to define the age of crystallization of this body with a robust, accurate and fast geochronological technique aiming to define the age of this magmatism event. Petrographic analyzes indicate that the studied batholith is constituted, predominantly, by granodiorites with biotite as dominant mafic and/or hornblende. Locally occur quartz monzodiorite, monzogranite, quartz monzonite, monzonite and syenogranite. The geochronological analysis was performed on a sample collected on the facets of the thinest edge of the pluton, which represents a hololeucocratic granodiorite. The U-Pb ages in zircon obtained (594 ± 12 Ma and 604.9 ± 8.6 Ma) using different degrees of agreement, overlap in the limit of the analytical errors with the previously published Rb-Sr isochronic age of 587 ± 19 Ma. Thus, Granodiorite Anil should not be correlated to the plutons of the Meruoca Intrusive Suite (~ 530 Ma), since there is an age difference of about 80 Ma between these two granitogens. Thus, Granodiorite Anil may be related to late granitoids that occur associated with the Tamboril-Santa Quitéria Complex.